An application of the Adomian's decomposition method to the analysis of MHD duct flows - Machado, J. M.; Verardi, SLL; Yang, S. Y. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
A new approach is proposed in this work for the treatment of boundary value problems through the Adomian's decomposition method. Although frequently claimed as accurate and having fast convergence rates, the original formulation of Adomian's method does not allow the treatment of homogeneous boundary conditions along closed boundaries. The technique here presented overcomes this difficulty, and is applied to the analysis of magnetohydrodynamic duct flows. Results are in good agreement with finite element method calculations and analytical solutions for square ducts. Therefore, new possibilities appear for the application of Adomian's method in electromagnetics.
Keywords: Adomian's decomposition method (ADM); homogeneous boundary conditions; magnetohydrodynamic (MHD) duct flows